Maskulinitas sebagai Tonggak Keempat dalam Kajian Feminisme Hubungan Internasional - Lulu Helina Mulya; Ani Soetjipto (Indonesian Perspective, 2021)
International relations as an academic field of study has a reputation for being masculine, violent, aggressive, or even brutal because of its focus on power projections and the state as the main actor. His academic and practical discussions rarely discuss issues related to other matters outside of defense, military, and state power, such as issues of gender equality or social welfare that have international and transnational dimensions. This paper criticizes the conception of masculinity which has been the heart of various schools of thought in international relations through the lens of feminism. This paper will explore more deeply the approaches and main ideas in the concept of masculinity and international relations, by focusing on the ideas promoted by the realism and constructivism paradigms. These ideas will then be contested with the concepts narrated by feminists in international relations. After reviewing the masculinity approach, this paper will also attempt to map the consensus between the feminist approach and the traditional notion of international relations regarding the concept of masculinity.